Effect of Home Enteral Nutritional Support Compared With Normal Oral Diet in Postoperative Subjects With Upper Gastrointestinal Cancer Resection: A Meta-Analysis - Liu, Fang; Pan, Xuling; Zhao, SuQing; Ren, RuiJun; Chang, GuiXia; Mao, Yu (Frontiers in Surgery, 2022)
Introduction We performed a meta-analysis to evaluate the influence of a home enteral nutritional support compared with a normal oral diet in postoperative subjects with upper gastrointestinal cancer resection. Methods A systematic literature search up to December 2021 was done and 23 studies included 3010 subjects with upper gastrointestinal cancer resection at the start of the study; 1556 of them were given home enteral nutritional support, and 1454 were normal oral diet. We calculated the odds ratio (OR) and mean difference (MD) with 95% confidence intervals (CIs) to evaluate the influence of home enteral nutritional support compared with normal oral diet in postoperative subjects with upper gastrointestinal cancer resection by the dichotomous or continuous methods with a random or fixed-influence model. Results Home enteral nutritional support had significantly higher quality of life (MD, 2.08; 95% CI, 1.50-2.67, p<0.001), better body weight change (MD, 1.87; 95% CI, 1.31-2.43, p<0.001), higher albumin (MD, 1.27; 95% CI, 0.72-1.82, p<0.001), and higher pre-albumin (MD, 30.79; 95% CI, 7.29-54.29, p=0.01) compared to normal oral diet in subjects with upper gastrointestinal cancer resection. However, home enteral nutritional support had no significant impact on the hemoglobin (MD, 4.64; 95% CI, -4.17-13.46, p=0.30), and complications (OR, 1.03; 95% CI, 0.76-1.40, p=0.83) compared to normal oral diet in subjects with upper gastrointestinal cancer resection. Conclusions Home enteral nutritional support had a significantly higher quality of life, better body weight change, higher albumin, and higher pre-albumin, and had no significant impact on the hemoglobin, and complications compared to normal oral diet in subjects with upper gastrointestinal cancer resection. Further studies are required.